Online Learning Platform Usage and Learning Intensity in EFL Students - Aprianto, Dedi; Muhlisin, Muhlisin (Indonesian Journal of Educational Science (IJES), 2024)
Seeing the current trends of rapidly growing uses of online learning tools within learning contexts becomes an instrument to understand the impact of learning tools on EFL students’ outcomes. The purpose of this study is to examine the correlation of online learning platforms and learning intensity and address the effectiveness of features and designs of online learning platforms in increasing students’ intensity. A mixed-method was used to obtaining the data form a sample size of 190 as the active users of the online learning platforms, selected through probability random sampling. Quantitative data was collected through a questionnaire, while qualitative data was collected from the excerpts of in-depth interviews conducted among subjects of the study. Data was analyzed by using Pearson product moment correlation, while the qualitative data, a thematic analysis technique was used. The results of the study reveal an extremely high correlation between the utilization of online learning platform tools and the intensity of learning English, with r = 0.973 and p < 0.001. Effective features supporting the strengthening of learning intensity, as qualitative findings suggest that effective features such as quizzes, discussion forums, interactive assignments, gamification, constructive feedback, collaboration, intuitive interface design, and diverse learning materials as key factors in increasing learning intensity. This study recommends enhancing online learning platforms with interactive features, gamification, constructive feedback, collaborative tools, responsive interface design, and diverse learning materials to boost English learning intensity among EFL students. Future research should explore the specific impacts of different platform types on student engagement and learning outcomes to further optimize platform effectiveness.